Pharmacological Potential of Bouea oppositifolia (Roxb.) Adelb. Leaves: Antioxidant, Antimicrobial and Membrane-Stabilizing Properties (Bangladesh Pharmaceutical Journal, 2025)
The present study investigates the antioxidant, antimicrobial, and membrane-stabilizing activities of methanolic extracts of leaves of Bouea oppositifolia (Plum Mango), an underexplored medicinal plant from the Anacardiaceae family. Various solvent fractions, including methanol (MESF), petroleum ether (PESF), dichloromethane (DCMSF), ethyl acetate (EASF), and aqueous (AQSF), were evaluated using in vitro assays. Antioxidant potential was assessed via total phenolic content (TPC) and DPPH free radical scavenging assays, revealing that DCMSF had the greatest TPC (221.69 mg GAE/g extract), while AQSF exhibited the strongest radical scavenging activity (IC50 = 0.03 μg/ml). Antimicrobial activity, determined through the disc diffusion method, demonstrated moderate inhibition against bacterial and fungal strains, with AQSF showing the most pronounced activity (12 mm inhibition zone). The membrane-stabilizing efficacy of the extracts was evaluated using hypotonic and heat-induced hemolysis assays, where MESF (38.52% inhibition) and EASF (60.35% inhibition) exhibited notable protective effects against erythrocyte lysis. These findings suggest that B. oppositifolia leaves possess potent antioxidant, antimicrobial, and membrane-protective properties, likely attributed to their rich phenolic and flavonoid content. This study highlights the plant’s pharmacological potential, requiring further phytochemical characterization and in vivo validation for drug development.Bangladesh Pharmaceutical Journal 28(2): 203-213, 2025 (July)